Online Objective Test Untuk Meningkatkan Layanan Unit Pelaksana Assessment Centre - Febriana Sariati Marpaung (Sekolah Tinggi Teknik - PLN, 2020)
Organizational changes in the PLN environment have an impact on business functions, one of which is the addition of new positions, both structural and functional. This condition influences the increasing number of assessment requests. Therefore it is necessary to make an effective service strategy to be able to provide fast and accurate services for users of assessment services. Online objective test as a solution to the problem. The analysis was carried out using the SWOT method and Weighted Ranking Decision. This test provides a significant efficiency for PLN in terms of time and cost. Also, PlN also has exclusive psychological testing material and is protected from copyright infringement, reduces the risk of leakage of test material, and enhances the company's image.